Paradendryphiella arenariae an endophytic fungus of Centella asiatica inhibits the bacterial pathogens of fish and shellfish - Shankar, Saranya; Sathiavelu, Mythili (Frontiers in Microbiology, 2024)
IntroductionAquaculture has been considered a major food-producing sector in the world during the last few decades. The foremost constraint in the development of aquaculture is bacterial disease control and management. Since various fish pathogens are resistant to conservative treatments, it is essential to screen new and effective alternative antibacterial agents. Endophytic fungi are microorganisms that live in the plant’s internal tissues without harming its host. Endophytic fungi have proven themselves as reliable sources of novel bioactive compounds that can be used as antibacterial agents.MethodsIn the present study, fifteen morphologically different endophytic fungi were isolated from the fresh and healthy stem section of Centella asiatica. The active endophytic fungal crude extracts were tested for agar well diffusion assay, Minimum Inhibitory Concentration, Minimum Bactericidal Concentration assays, Time-kill kinetic analysis, Brine shrimp lethality assay.Results and DiscussionAgar plug diffusion and agar well diffusion assays revealed that endophytic fungus CAS1 exhibits maximum antagonistic activity against bacterial fish pathogens. The ethyl acetate crude extract of CAS1 exhibited the maximum zone of inhibitions against Aeromonas hydrophila (21  ±  0.11  mm), Aeromonas caviae (18  ±  0.1  mm), Edwardsiella tarda (23  ±  0.11  mm), Vibrio anguillarum (19  ±  0.05  mm) and Vibrio harveyi (20  ±  0.27  mm). The MIC and MBC values extract varied reliant on the trial pathogens ranging between 12.5-100 μg/mL and 25-100μg/mL correspondingly. The morphological and molecular characterization of potential isolate CAS1 was confirmed as Paradendryphiella arenariae by 18S rRNA ITS gene sequencing with 99.18% identity. This is the foremost findings to study the antagonistic effect of Paradendryphiella arenariae isolated from the stem of Centella asiatica against bacterial fish pathogens which can be used as natural effective antibacterial agents in aquaculture.